Pemenuhan Ham Pada Anak Panti Asuhan Jernih Balaki Indonesia (Universitas Gresik, 2023)
The Orphanage is a gathering place for children who are entrusted with their parents, children are entrusted by their parents for their own reasons. The orphanage in Born without the guidance of biological parents did not make them give up, even so the children in the orphanage have a high enthusiasm for learning. The orphanage must be able to provide the rights and fulfillment of children according to statutory provisions. This research is qualitative, data obtained directly to the location and analyzed critically. The orphanage consists of coaches, supervisors, chairmen, secretaries, treasurers, caregivers. The Clear Balaki Indonesia Orphanage consists of 21 children. And has been established since March 2022.